2019
DOI: 10.5194/se-2019-69
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A revised map of volcanic units in the Oman ophiolite: insights into the architecture of an oceanic proto-arc volcanic sequence

Abstract: Abstract. Recent studies have revealed genetic similarities between Tethyan ophiolites and oceanic proto-arc sequences formed above nascent subduction zones. The Semail ophiolite (Oman–U.A.E.) in particular can be viewed as an analogue for this proto-arc crust. Though proto-arc magmatism and the mechanisms of subduction-initiation are of great interest, insight is difficult to gain from drilling and limited surface outcrops in submarine fore-arcs. In contrast, the Semail ophiolite, in which the 3–5 km thick up… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(24 citation statements)
references
References 100 publications
(371 reference statements)
1
23
0
Order By: Relevance
“…Pristine volcanic glasses are exceedingly rare in the Samail lavas (Kusano et al., 2017). Our field sampling throughout the Samail ophiolite (Belgrano et al., 2019) confirmed that glass is rare, but is most likely to be preserved in areas with sub‐greenschist facies hydrothermal alteration, hence mostly within the upper Alley group volcanic units (Figure 2). All the glasses we collected from the axial Geotimes lavas were subtly affected by secondary hydration, though one pristine glass was recovered from Axial Lasail lavas intercalated within the uppermost axial Geotimes sequence, near similar intercalations along Wadi Fizh (Belgrano & Diamond, 2019).…”
Section: Samples Methods and Datasupporting
confidence: 55%
See 3 more Smart Citations
“…Pristine volcanic glasses are exceedingly rare in the Samail lavas (Kusano et al., 2017). Our field sampling throughout the Samail ophiolite (Belgrano et al., 2019) confirmed that glass is rare, but is most likely to be preserved in areas with sub‐greenschist facies hydrothermal alteration, hence mostly within the upper Alley group volcanic units (Figure 2). All the glasses we collected from the axial Geotimes lavas were subtly affected by secondary hydration, though one pristine glass was recovered from Axial Lasail lavas intercalated within the uppermost axial Geotimes sequence, near similar intercalations along Wadi Fizh (Belgrano & Diamond, 2019).…”
Section: Samples Methods and Datasupporting
confidence: 55%
“…Magmatism along a seafloor spreading axis formed much of the lower crust as well as the sheeted‐dike complex and comagmatic “ Geotimes ” basal lava unit (Pearce et al., 1981; Umino et al., 1990). These dikes and lavas are similar in trace element composition to mid‐ocean ridge basalts (MORB), but show a broader range of SiO 2 compositions and are subtly contaminated by a hydrous subduction component (Belgrano et al., 2019; MacLeod et al., 2013; Pearce et al., 1981). Locally, axial magmatism was more substantially contaminated by subduction fluids, resulting in the eruption of high Th/Nb “ Axial Lasail ” basalts depleted in incompatible trace elements (Belgrano & Diamond, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Belgrano et al. (2019) recently published a comparison of trace element data from the two localities. They note differences in the trace element compositions of the Samail and IBM forearc lavas—including higher Ti/V in Samail V1 versus IBM forearc basalts and elevated Zr in IBM boninites—which they argue may be related to prior depletion of the mantle wedge in the IBM and differences in the composition of subducted crust.…”
Section: Discussionmentioning
confidence: 99%